Voicing the Silence: Womanhood in ManjuKapur‟s Home - Viswanathan, Vidhya (International Journal of Psychosocial Rehabilitation, 2020)
Delegates of the socio-political movement, feminism, have formulated a school of thought that focus on the welfare of women in society. Critics and theorists including Simone de Beauvoir, Mary Wollstonecraft, Julia Kristeva, Helene Cixous, Luce Irigaray, Kate Millet and Elaine Showalter have voiced those silent aspects related to the predicament of women in a patriarchal society. They have discussed and debated on aspects such as the marginalization of women, their quagmire in patriarchal society and spatial justice with respect to women across the globe.In spite of all thesereverberations raised on the mantle of gender equality and gender politics with respect to the condition of women, true feminine experiences and expressions are still suppressed and silenced in the tangles of cultural conditioning. In this scenario there is a need to lend an ear to those agonies and anguish experienced by women in the gendered role plays set within the matrix of the patriarchal system. The eminent post colonial Indian English writer, ManjuKapur , exhibits the dilemma, susceptibility, vulnerability and identity crisis experienced by women folk in different gendered roles that are bound by time and space. In this context, this paper is an attempt to bring forth the predicament of women in a gendered society with respect to the novel, Home by ManjuKapur.